The Effects of Location and MNC Attributes on MNCs' Establishment of Foreign R&D Centers: Evidence from China. Issue 5 (October 2016) - Holmes, R. Michael; Li, Haiyang; Hitt, Michael A.; DeGhetto, Kaitlyn; Sutton, Trey
Abstract : This study examines factors affecting MNCs' establishment of R&D centers in China (i.e., China R&D centers). We argue that China offers not only location advantages (e.g., economic growth) that encourage MNCs to establish R&D centers there, but also location disadvantages (e.g., weak intellectual property protection) that discourage MNCs from doing so. Examining a sample of China R&D centers established by U.S. MNCs over fifteen years, we find that China's location advantages and location disadvantages have both independent and joint effects on MNCs' establishment of China R&D centers. We also find that MNC attributes moderate these effects.